Design of welded stainless steel I-shaped members subjected to shear. (January 2020) - Chen, X.W.; Real, E.; Yuan, H.X.; Du, X.X.
Abstract: This paper aims to develop design methods for the shear strength of welded stainless steel I-shaped members. The current American AISC Design Guide 27 has been published for Structural Stainless Steel, and it refers to the specification ANSI/AISC 360-16 for structural steel buildings for the shear strength without considering tension field action (TFA). All the available test data on stainless steel plate girders were collected from literatures and employed to assess the provisions in the Design Guide 27, as well as the codified ones in Eurocode 3 Part 1.4. Based on the test results and obtained comparisons, two new proposals for unstiffened webs or webs with transverse stiffeners widely spaced (without TFA), and for interior webs with stiffeners spaced at 3 h w or smaller (considering TFA) were developed and presented to match the format of the expressions in ANSI/AISC 360-16 for stainless steel webs under shear. Reliability analysis was further performed to calculate the Load and Resistance Factor Design (LRFD) resistance factors determined by the new proposals and to further justify the target factor in AISC Design Guide 27 for structural stainless steel. Highlights: Summary of existing tests on stainless steel I-shaped members subjected to shear. Assessment of codified design methods for predicting shear strengths. New proposal for the critical shear buckling strength of stainless steel webs. New design methods for the shear strength without TFA and considering TFA. Statistical analysis to verify the reliability of new design proposals.